Observation of a Fully-formed Forward–Reverse Shock Pair due to the Interaction between Two Coronal Mass Ejections at 0.5 au - Trotta,D; Dimmock,AP; Blanco-Cano,X; Forsyth,RJ; Hietala,H; Fargette,N; Larosa,A; Lugaz,N; Palmerio,E; Good,SW; Soljento,JE; Kilpua,EKJ; et al. (The Astrophysical Journal Letters, 2024)
Abstract We report direct observations of a fast magnetosonic forward–reverse shock pair observed by Solar Orbiter on 2022 March 8 at the short heliocentric distance of 0.5 au. The structure, sharing some features with fully-formed stream interaction regions, is due to the interaction between two successive coronal mass ejections (CMEs), never previously observed to give rise to a forward–reverse shock pair. The scenario is supported by remote observations from extreme ultraviolet cameras and coronagraphs, where two candidate eruptions compatible with the in situ signatures have been found. In the interaction region, we find enhanced energetic particle activity, strong nonradial flow deflections, and evidence of magnetic reconnection. At 1 au, well radially aligned Wind observations reveal a complex event, with characteristic observational signatures of both stream interaction region and CME–CME interaction, thus demonstrating the importance of investigating the complex dynamics governing solar eruptive phenomena.